The Myth of Ham in Nineteenth-Century American Christianity: Race, Heathens, and the People of God (Conversations in religion and theology, 2006)
Books reviewed: The Myth of Ham in Nineteenth-Century American Christianity: Race, Heathens, and the People of God, Sylvester A. Johnson Reviewed by Stephen G. Ray, Jr. The Lutheran Theological Seminary, Philadelphia, USA Response to Stephen Ray, Jr. By Sylvester A. Johnson Florida A & M University, USA